Dosage Effectiveness of the Combination Calcium Hydroxide-Propolis as an Inhibitor for Aggregatibacter actinomycetemcomitans Biofilm - Ira Widjiastuti; Moch. Mudjiono; Nancy Cynthia Sudiartha; Grace Angelina Samuel; Ni Putu Sawitri Mega (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: Calcium hydroxide is widely used as pulp-capping material, but it is resistant to Aggregatibacteractinomycetemcomitans bacteria. Because of this deficiency, many researchers are considering usingalternative natural ingredients, such as propolis. Propolis has been widely used in dentistry due to itsproperties and because it has active ingredients that can act as antibacterial agents. It is hoped that whencalcium hydroxide and propolis are combined, the combination can overcome the disadvantages. The aim ofthis study was to determine the dosage effectiveness of the combination calcium hydroxide-propolis as aninhibitor for A. actinomycetemcomitans biofilm. Material and methods: The sample was divided into fivegroups. The positive control group is a combination of calcium hydroxide-sterile aquadest, and the negativecontrol group is A. actinomycetemcomitans bacteria. Group I is a combination of calcium hydroxidepropolis with a ratio of 1:1, group II has a ratio of 1:1.5, and group III has a ratio of 1:2. Each group consistsof five replications. Combination of calcium hydroxide-propolis and A. actinomycetemcomitans bacterialsuspension was incubated for 2x24 hours then washed three times using PBS. Furthermore, 2% of crystalviolet was used for staining and covered with aluminum foil and then incubated for 15 minutes. Isopropanol200µL was added, followed by a measurement of OD with an ELISA reader, and the OD values werecalculated using an inhibition biofilm formula. Results: Group II has the largest mean inhibition with 76%compared to groups one and three. Conclusion: A combination of calcium hydroxide and propolis with aratio of 1: 1.5 is more effective than 1:1 or 1:2 to inhibit A. actinomycetemcomitans biofilm.